Pathologic characteristics of immunologic injury in primary cultured rat hepatocytes and protective effect of glycyrrhizin in vitro - Zheng Qin-Zhu; Lou Yi-Jia (Acta Pharmacologica Sinica; Vol 24, No 8 (August 2003): Acta Pharmacologica Sinica, 2016)
AIM: To explore the pathologic characteristics of immunologic injury in primary cultured rat hepatocytes, and to evaluate the protective effect of glycyrrhizin (Grz) in vitro. METHODS: Sprague-Dawley rats were initiated with BCG vaccine in vivo, and then the primary cultured rat hepatocytes were stimulated with lipopolysaccharides (LPS) 10 mg/L in vitro (BCG+LPS treatment), the hepatoprotection by Grz was evaluated in the hepatocytes treated as above. Supernatant AST and LDH activities were measured, and nitric oxide (NO) was evaluated by Giress reaction. Aminoguanidine was used to confirm the target of Grz action. Expression of intercellular adhesion molecular-1 (ICAM-1) was determined by immunocytochemistry. Percentage of apoptosis was detected with fluorescence microscope and flow cytometer. RESULTS: In LPS-treated group, supernatant AST was not increased compared with that in control, while supernatant AST and LDH in BCG+LPS treatment were increased significantly (P